Mobilized: women and mobile communications in Spain - Inmaculada José Martínez Martínez; Juan Miguel Aguado Terrón; Iolanda Tortajada Giménez (Feminismo/s, 2009)
Despite being traditionally consigned to a secondary place in the discourses on the Information Society, few technologies have such an intensive and extensive social impact as mobile communications. Beyond figures, the mobile telephone has introduced radical qualitative changes in social interaction rituals and in everyday identity management. Its deep implication in everyday life makes mobile telephone a relevant phenomenon to take into account in the analysis of women’s appropriation of technology, that is, the inclusion of ICTs in gendered identity building and management practices. Beyond the studies focused on usage figures, this paper analyzes and compares the perceptions of productive agents in the mobile communication sector and women users about the integration of technology in their everyday management of identity.